Scoping Review: Hambatan Penerapan Telemedicine di Indonesia - Kharisma Firda Amalia; Eka Hendryanny; Herry Garna (Bandung Conference Series: Medical Science, 2022)
Abstract. Telemedicine is a long-distance health service using telecommunications media. The use of telemedicine is currently increasing during the COVID-19 pandemic due to the social restrictions implemented to avoid wider exposure of the virus. This study uses a scoping review method. The search of the articles is conducted using the Google scholar database and other published articles. There are 60 articles found and among them are 4 articles that meet the criteria. The application of telemedicine in Indonesia has not been carried out optimally because it is still constrained by inadequate infrastructure and the quality of the internet network that has not been comprehensive throughout Indonesia. Abstrak. Telemedicine merupakan layanan kesehatan jarak jauh menggunakan media telekomunikasi, penggunaan telemedicine saat ini terus mengalami peningkatan, peningkatan terjadi pada masa pandemik COVID-19 karena pembatasan sosial agar tidak terjadi paparan yang lebih luas. Penelitian ini menggunakan metode scoping review. Pencarian artikel mengunakan database Google scholar dan artikel lainnya yang dipublikasikan. Terdapat 60 artikel dan 4 artikel yang sesuai dengan kriteria. Penerapan telemedicine di Indonesia belum dilakukan secara maksimal karena masih terkendala insfrastruktur yang belum memadai dan kualitas jaringan internet yang belum menyeluruh di seluruh wilayah Indonesia.